(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: Lecture is an important method of instruction through which the undergraduate medical students acquire knowledge, experience, skill and attitude. There are however, serious questions regarding the effectiveness of the traditional lecture approach. Yet, it is agreed upon that this can be more effective by making this approach methodical and more interactive. Objectives: This study was conducted to assess medical teachers skills in instructional events in their lecture classes. Materials and Methods: A descriptive, crosssectional study was conducted from July 2013 to June 2014 at conveniently selected six medical colleges of the country. At those selected institutions 30 lecture classes were observed and views of 1500 students were collected. A checklist with rating scale having rubric was used by the researchers to record the necessary observations while attending the lectures covering 8 instructional events. Out of 30 lecture classes, 13 were of preclinical subjects and 17 were of paraclinical area. Views of 1500 students were collected on a self administered structured questionnaire just after attending observed classes, covering 11 areas of performance. Out of them 732 were preclinical students and 768 were paraclinical students. Results: In this study, majority of the respondents (67%) agreed that the teachers successfully gained attention. In mentioning objective, the observer marked more than half (53.3%) of the teachers as unsatisfactory. The mean score of observers opinion in mentioning objective was 0.97±1.35. More than one fourth (23.55%) of the student respondents did not agree that the teachers stimulated prior knowledge in the lecture class. More than one fourth (26.15%) of the respondents did not agree that necessary feedback were taken by the teachers. Forty two percent of the respondents did not agree that the teachers provided a good summary at the end. More than one fourth of the respondents (26.85%) did not agree that the lecture was interesting. In this study, some of the key performances of the teachers like mentioning objective of the lesson, providing summary, legibility of teaching aids were scored less than 2, indicating that those were the problem areas and should be emphasized more. In this regards, continued medical education/continued professional developmental program of medical colleges should be valued and exercised properly. Conclusion: Effectiveness of a lecture largely depends on the knowledge of the teachers in teaching methodologies, their individual skills in presentation and their ability in classroom management. This study revealed that the teachers of medical colleges had been missing some important characteristics of effective lecture. Journal of Armed Forces Medical College Bangladesh Vol.11(1) 2015: 19-24